1996
DOI: 10.1002/hep.510240226
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhotic Cardiomyopathy: Getting to the Heart of the Matter

Abstract: can lead to liver dysfunction and damage. How unexpected In cirrhosis, cardiac contractile function has been exand gratifying, therefore, to find a voice as eloquent as the tensively documented to be abnormal. At baseline, carlate Chilean Nobel laureate's to not only extoll the many diac output is increased, and this is one of the charactervirtues of the liver, but also remind us that sometimes the istics of hyperdynamic circulation. However, when liver takes precedence over the heart, i.e., that liver failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
239
1
14

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(259 citation statements)
references
References 98 publications
5
239
1
14
Order By: Relevance
“…Some studies have demonstrated that bile salts affect heart contractility. 32 Because we have previously demonstrated a clear correlation between ET-1 plasma concentrations and bilirubin levels in cirrhotic patients by multiple regression analysis, 5 there may be more marked effect of an ET-1 antagonist in secondary biliary cirrhosis rats with high plasma bilirubin levels.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies have demonstrated that bile salts affect heart contractility. 32 Because we have previously demonstrated a clear correlation between ET-1 plasma concentrations and bilirubin levels in cirrhotic patients by multiple regression analysis, 5 there may be more marked effect of an ET-1 antagonist in secondary biliary cirrhosis rats with high plasma bilirubin levels.…”
Section: Discussionmentioning
confidence: 93%
“…This phenomenon has been termed cirrhotic cardiomyopathy and is believed to be caused by a combination of factors, including impairment of cardiac ␤-adrenergic receptors, changes in the properties of the cardiac cell membrane, abnormalities in circulating humoral factors, and ventricular overload induced by the hyperdynamic circulation. 10 It is also known that intraoperative manipulation of the liver during OLT releases cytokines and endotoxins that mediate an inflammatory response. 11,12 In animal studies, infusion of these cytokines has been shown to cause myocardial depression.…”
Section: Discussionmentioning
confidence: 99%
“…Estas alteraciones hemodinámicas predicen una supervivencia menor en estos pacientes (6). Estos pacientes también presentan modificaciones cardiacas subclínicas como una disfunción diastólica y disminución de la contractilidad cardiaca con el esfuerzo físico o cuando son sometidos a una sobrecarga farmacológica, lo que puede contribuir al empeoramiento de las alteraciones hemodinámicas sistémicas (7,8). Ma y Lee fueron los primeros en describir esta miocardiopatía (8), que se asocia a la aparición de áreas de fibrosis ventricular, focos de edema e hipertrofia o dilatación (9,10).…”
unclassified